2016
DOI: 10.1002/jcad.12091
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mental Health Among College Students in Guam: Implications for Counseling

Abstract: The authors investigated sociodemographic predictors of the mental health status of college students (N = 308) in Guam. Results indicated prevalence rates of 17.8%, 40.2%, and 25.6% for moderate or more severe levels of depression, anxiety, and stress, respectively. Psychological distress was found to be predicted by gender, ethnicity, living arrangement, and academic level. Comparisons with college students in the U.S. mainland and Hong Kong were also examined. Implications for counseling services and strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
2
19
0
2
Order By: Relevance
“…Our findings that some types of stressors are more likely to negatively impact mental health than others and that those impacts may vary by gender have important implications for colleges and professionals concerned about the mental well being of college students. For example, although significant (and legitimate) concerns about the cost of college and student debt have been expressed by students, families, and some researchers (Ran et al, 2016;Saïas et al, 2014), our results suggest that financial pressures may not negatively affect the mental health of students. That does not mean that the financial impacts of rising costs and debt should be ignored, but it does mean that efforts to address mental health problems in college students may not benefit much from focusing on helping students to cope with financial stressors.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Our findings that some types of stressors are more likely to negatively impact mental health than others and that those impacts may vary by gender have important implications for colleges and professionals concerned about the mental well being of college students. For example, although significant (and legitimate) concerns about the cost of college and student debt have been expressed by students, families, and some researchers (Ran et al, 2016;Saïas et al, 2014), our results suggest that financial pressures may not negatively affect the mental health of students. That does not mean that the financial impacts of rising costs and debt should be ignored, but it does mean that efforts to address mental health problems in college students may not benefit much from focusing on helping students to cope with financial stressors.…”
Section: Discussionmentioning
confidence: 58%
“…Stressors such as job insecurity, high pressure or excessive workloads, and performanceavoidance goals have also been shown to be related to depression and anxiety in both women and men (Fan, Blumenthal, Watkins, & Sherwood, 2015;Lavasani, Khezriazar, Amani, & Malahmadi, 2011;Melchior et al, 2007). Finally, financial stress was shown to be associated with psychological distress in one study (Ran et al, 2016;Saïas et al, 2014) but not in another (Verger et al, 2009).…”
Section: Stress Mental Health Symptoms and Help-seeking In College mentioning
confidence: 97%
See 1 more Smart Citation
“…De manera similar, Pekmezovic et al (2011) hallaron que los jóvenes que vivían con sus padres obtuvieron mayores puntuaciones en todas las dimensiones de los CSF y CSM. Ran et al (2016) reportaron que los estudiantes que vivían solos se encontraban en mayor riesgo de presentar depresión que quienes vivían con sus padres. En ese sentido, los estudios han señalado la importancia del soporte social para la salud mental y física en estudiantes universitarios (Córdova, 2015;DeBerard & Masters, 2014;Feldman et al, 2008).…”
Section: Discussionunclassified
“…The onset of most mental health disorders is during young adulthood [6]. Various studies have reported that 40 million of adults in the United States have anxiety disorder, of which 75% of them experienced their rst episode by age 22, a typical college age [7], and over half of college students in the country had at least one mental health problem [8]. Similarly, more than 20% of university students in Hong Kong live with either depression, anxiety, or stress [9].…”
Section: Introductionmentioning
confidence: 99%